Toxic Voices : The Villain from Early Soviet Literature to Socialist Realism - Laursen, Eric, 1957- (Book collections on Project MUSE., 2013)
Satire and the fantastic, vital literary genres in the 1920s, are often thought to have fallen victim to the official adoption of socialist realism. In this book, the author contends that these subversive genres did not just vanish or move underground. Instead, key strategies of each survive to sustain the villain of socialist realism. The author argues that the judgment of satire and the hesitation associated with the fantastic produce a narrative obsession with controlling the villain's influence. In identifying a crucial connection between the questioning, subversive literature of the 1920s and the socialist realists, the author produces an insightful revision of Soviet literary history.